Evaluation of Lilium Hybrids (Lilium x hybrida) for Growth, Flowering and Bulb Attributes in the Hilly Regions of Uttarakhand - Narendra Singh Bhandari (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
The present study was initiated to elucidate performance of 18 exotic lilium hybrids (Lilium x hybrida) to assess their suitability for commercial cultivation in the hilly regions of Uttarakhand. The investigation was carried out at Jilling Floritech farm during 2014-15 under protected conditions in Randomised Block Design. All the 18 hybrid varieties showed significant variation for vegetative, flowering and bulb attributes. Analysis of data indicated that among the cultivars studied, earliest sprout emergence (4.66 days) was recorded in 'Yellow Diamond'. Earliest flower-bud initiation (30.33 days) was recorded in 'Bach', and flower-bud colour break stage (46.33 days) and flowering (50.00 days) in 'Detroit'. Maximum number of flower buds/plant (8.66) was recorded in 'Pollyana', longest inflorescences (25.23cm) in I'ndian Summerset', maximum flower diameter (17.66cm) in 'Creil' and 'Golden Tycoon', maximum plant height (145.13cm) in 'Bright Dimond', and maximum stem thickness (1.86cm) in 'Novana'. However, maximum number of bulblets (6.66) per plant was recorded in 'Ceb Dazzle'.